(untitled) (Iter, 2022)
Cussen is the author ofa book of verses where he introduces Maecenas, the renowned counselor andfriend of Augustus*, dictating some poem-letters for Virgil and the emperor to his secretary. In them Rome lives the splendor o f its glory and the tiredness ofits decline, and the characters discover the depth ofits soul within the framework ofa historical happening devoid of melancholy.